Multiscale 3D characterization with dark-field x-ray microscopy. (8th June 2016) - Simons, Hugh; Jakobsen, Anders Clemen; Ahl, Sonja Rosenlund; Detlefs, Carsten; Poulsen, Henning Friis
Abstract: Abstract : Dark-field x-ray microscopy is a new way to three-dimensionally map lattice strain and orientation in crystalline matter. It is analogous to dark-field electron microscopy in that an objective lens magnifies diffracting features of the sample; however, the use of high-energy synchrotron x-rays means that these features can be large, deeply embedded, and fully mapped in seconds to minutes. Simple reconfiguration of the x-ray objective lens allows intuitive zooming between different scales down to a spatial and angular resolution of 100 nm and 0.001°, respectively. Three applications of the technique are presented—mapping the evolution of subgrains during the processing of plastically deformed aluminum, mapping domains and strain fields in ferroelectric crystals, and the three-dimensional mapping of strain fields around individual dislocations. This ability to directly characterize complex, multiscale phenomena in situ is a key step toward formulating and validating multiscale models that account for the entire heterogeneity of materials.